The heart of everything that is : the untold story of Red Cloud, an American legend - Drury, Bob (Simon & Schuster, 2013)
The untold story of the great Ogala Sioux chief Red Cloud, the most powerful Indian commander of the Plains who witnessed the opening of the West and forced the American government to sue for peace in a conflict named for him.